Adsorptive Removal of Chemical Oxygen Demand Using Eggshells and Tea Waste Entrapped in Calcium Alginate - Zulaikhah Fatmawati; Vita Paramita; Hermawan Dwi Ariyanto (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2023)
This study aims to assess the efficiency of two agricultural wastes as biosorbents to remove the chemical oxygen demand (COD) from a batik wastewater sample. COD-containing batik wastewater was treated with a combination of biosorbents by eggshells and tea waste activated using H?SO? and then immobilized in calcium alginate through the entrapment technique. The contact time, pH, and biosorbent dose were all investigated to examine the efficiency of biosorbent to remove COD. The independent variables for the optimization process are the contact time (47.13, 50, 60, 70, and 72.87 min), pH of the samples (1.71, 2,3, 4, and 4.28), and the ratio of the number of biosorbent between eggshells: tea waste (2.67:12.33, 3.75:11.25, 7.5:7.5, 11.25:3.75, and 12.33:2.67). The Characterization of the biosorbents was investigated using scanning electron microscopy (SEM), Fourier transforms infrared spectroscopy (FTIR), and energy-dispersive x-ray (EDX) analysis. The results show that eggshells and tea waste immobilized by calcium alginate with a ratio of 2.67 g: 12.33 g, a contact time of 60 min, and a sample pH of 3 are 89% effective in removing the COD in batik wastewater samples.